Population pharmacokinetic modeling of PF-06439535 (a bevacizumab biosimilar) and reference bevacizumab (Avastin(®)) in patients with advanced non-squamous non-small cell lung cancer - Li, Cheryl S. W. (Cancer Chemother Pharmacol, 2019)
PURPOSE: The objectives of this analysis were to characterize the population pharmacokinetics (PK) of PF-06439535 (a bevacizumab biosimilar) and reference bevacizumab (Avastin(®)) sourced from the European Union (bevacizumab-EU) in patients with advanced non-squamous non-small cell lung cancer (NSCLC), and to quantify the difference in PK parameters between the two drug products via covariate analysis. METHODS: Pooled PF-06439535 and bevacizumab-EU serum concentration data from a comparative clinical efficacy and safety study (NCT02364999) in patients with NSCLC (N = 719) were analyzed using a non-linear mixed-effects modeling approach. Patients received PF-06439535 plus chemotherapy or bevacizumab-EU plus chemotherapy every 21 days for 4–6 cycles, followed by monotherapy with PF-06439535 or bevacizumab-EU. PF-06439535 or bevacizumab-EU was administered intravenously at a dose of 15 mg/kg. Effects of patient and disease covariates, as well as the drug product (PF-06439535 versus bevacizumab-EU), on PK were investigated. RESULTS: Overall, 8632 serum bevacizumab concentrations from 351 patients in the PF-06439535 group and 354 patients in the bevacizumab-EU group were included in the analysis. A two-compartment model adequately described the combined data. Clearance (CL) and central volume of distribution (V(1)) estimates were 0.0113 L/h and 2.99 L for a typical 71-kg female patient with NSCLC administered bevacizumab-EU. CL and V(1) increased with body weight and were higher in males than females even after accounting for differences in body weight. The 95% confidence intervals for the effect of drug product on CL and V(1) encompassed unity. CONCLUSIONS: The population PK of PF-06439535 and bevacizumab-EU were well characterized by a two-compartment model. Covariate analysis did not reveal any appreciable differences between PK parameters for PF-06439535 and bevacizumab-EU in patients with NSCLC. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT02364999. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00280-019-03946-8) contains supplementary material, which is available to authorized users.